New Insights into the Prevalence of Dirofilaria immitis in Hungary - Ákos Jerzsele; Dóra Kovács; Péter Fábián; Péter Fehérvári; Bettina Paszerbovics; Krisztina Bali; Eszter Kaszab; Nóra Mayer; Zita Karancsi (Animals)
Heartworm disease—caused by Dirofilaria immitis—is an emerging mosquito-borne zoonotic disease with potentially fatal outcomes in dogs. Due to factors such as climate change, animal importation, and animal transport, the prevalence of the infection has increased in countries in Central and Eastern Europe, where the parasite was not detected before. The first autochthonous case of D. immitis in dogs in Hungary was reported in 2009. This study assessed the prevalence of D. immitis infection and the associated risk factors in domestic dogs in Hungary. A total of 1071 blood samples were collected between March 2023 and February 2024 and were tested using Knott’s test, ELISA, and real-time PCR method. The countrywide prevalence of D. immitis was 17.0%, suggesting a continuous increase in the parasite’s spread compared to the previously reported 11.3% prevalence, with age and spending time outdoors being the main risk factors. These results highlight the ongoing need for preventive measures against heartworm disease.